2020
DOI: 10.24815/siele.v7i1.15032
|View full text |Cite
|
Sign up to set email alerts
|

Lexical richness of newspaper editorials published in Southeast Asian countries

Abstract: This paper investigates the lexical richness of newspaper editorials written by the writers from ESL (English as a Second Language) and EFL (English as a Foreign Language) of Southeast Asian countries. Using editorial texts published on the same day in two major online newspapers from Malaysia and the Philippines as representative of ESL countries, and two major online newspapers published in Indonesia and Thailand that represent EFL countries, this paper compares the production of Type Token Ratio (TTR) as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…It means that none of the null hypotheses was rejected. The results of this study were consistent with Indarti (2020), who pointed out that lexical richness in newspaper editorials by ESL and EFL was insignificant, with a slightly higher score in the ESL group. Similarly, ESL writers of this study demonstrated higher levels of English proficiency in using varied vocabulary than that of EFL in several aspects.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It means that none of the null hypotheses was rejected. The results of this study were consistent with Indarti (2020), who pointed out that lexical richness in newspaper editorials by ESL and EFL was insignificant, with a slightly higher score in the ESL group. Similarly, ESL writers of this study demonstrated higher levels of English proficiency in using varied vocabulary than that of EFL in several aspects.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, ESL writers of this study demonstrated higher levels of English proficiency in using varied vocabulary than that of EFL in several aspects. In this case, Indarti (2020) explained that this finding could be clearly understood due to English was more broadly used in education and governance policy in ESL countries. As a result, these writers possessed advantages from English status and abundantly supportive environments to strengthen and cultivate their English competency more effectively.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The language itself is as a medium of the study to learn such context related to linguistics. Many studies include news articles as their objects of observation (Indarti, 2020;Msuya, 2020;Olugbenga, 2020;Ziyayeva, 2020). The writer provides more explanation of phrasal verbs by giving the tree diagram in order to be more explicitly described.…”
Section: Introductionmentioning
confidence: 99%
“…Both the patterns and types are the tools to frame the writing as the authors wish the readers to see, so they have similar ideas in mind. Many studies include news articles as their objects of observation (Indarti, 2020;Msuya, 2020;Olugbenga, 2020;Ziyayeva, 2020). However, to the best of our knowledge, the study on sentence patterns and types in newspaper articles is not extensively explored yet.…”
Section: Introductionmentioning
confidence: 99%